O ensino a partir da etnomatemática na perspectiva da educação ambiental - Ferrete, Rodrigo Bozi (2016)
National assessments for the teaching and learning of mathematics have indicated that Brazilian students have, in general, a low school performance in this discipline. One of the reasons discussed to justify this performance is the abstract characteristic of how this knowledge is worked in the classroom, since these avaliations indicate, generally, that the teaching of this discipline is characterized by a theoretical knowledge unrelated to the student everyday. In order to contribute to these discussions, this study aims to understand how Ethnomathematics contributes to the development of education in environmental perspective, able to promote knowledge valid for the formation of a critical individual, participatory and co-responsible for the environment. For that, a qualitative research was carried out, developed through intervention in Mathematics II, of the Integrated Building Course, Campus of Aracaju, the Federal Institute of Sergipe, where the teaching activities of the content of mathematics were drawn from the theoretical conceptions of Ethnomatematics and Critical Environmental Education. The datas were interpreted by following the concepts of Discourse Analysis. In theory, it was found that Ethnomathematics and Critical Environmental Education have a strong influence of the educational proposal of Paulo Freire and thus have common elements as well as additional features that favor the joint work of them, since one complements the other. The Ethnomathematics open educational space for the Critical Environmental Education to develop, while the second extends the research of the first, bringing concern for the production environment, social and political conditions in which the knowledge is produced. Through the empirical data it was concluded that all these two lines of research, worked from the pedagogical problematic practice, based on dialogue with the students, made possible a favorable teaching the development of a critical environmental awareness of the reality of each of them; more complex understanding of the importance and significance of mathematics; motivation to participate and attend the math class, interest to continue researching more information about the issues covered in class; increased self-esteem related to the ability and the knowledge they possess; development of critical thinking to understand the problems of their daily lives; responsibility and autonomy development as active citizens of society.